Effect of different farming systems on physiological response, blood parameters and endocrinological profiles in Deccani sheep - KOCHEWAD, S A; RAGHUNANDAN, T; RAO, K SARJAN; REDDY, K KONDAL; KUMARI, N NALINI; RAMANA, D B V; BALAMURGAN, T C; KANKARNE, YOGESHWAR; KUMAR, SANJEEV; MEENA, L R (The Indian Journal of Animal Sciences, 2017)
The result from revealed that T3 group have significantly (P<0.05) higher respiratory rate, pulse rate and rectal temperature than T1 and T2 groups. Similarly T1 group has significantly (P<0.05) higher Haemoglobin concentration than T2 and T3 groups. Packed cell volume revealed, T3 group has significantly (P<0.05) higher value than T2 and T1 groups. T1 and T2 groups have significantly higher glucose concentration than in T3 group. Similar observation was reported in total protein content. SGOT concentration revealed that significant (P<0.05) difference was observed among the groups and T3 group has significantly higher value than other groups whereas SGPT level was significantly higher in T3 and T2 groups than in T1 groups. Endocrinological profiles such as (T3) triiodothyronine and (T4) thyroxine revealed that T1 group have significantly higher level than T2 and T3 groups and T2 group had significantly (P<0.05) higher T3 and T4 value than in T3 group. Similarly, significantly (P<0.05) higher cortisol was recorded in T3 group over T2 and T1 groups and T2 and T1 groups were comparable. It was found that the intensive system of rearing has higher beneficial effect on comfort and productive performance for sheep farming in the tropical conditions. In the other 2 systems, the stress need to be reduced by supplementation of higher plane of nutrition, electrolyte supplementation during extreme summer and creation of waterbodies in the path of grazing and provision of shade and shelter for the sheep flocks while on long hours of grazing are essential.